A prospective study on neurocognitive effects after primary radiotherapy in high-grade glioma patients - Bodensohn, Raphael; Corradini, Stefanie; Ganswindt, Ute; Hofmaier, Jan; Schnell, Oliver; Belka, Claus; Niyazi, Maximilian (International Journal of Clinical Oncology, 2016)
Background: Neurocognition is a very important aspect of a brain tumor patient’s quality of life following radiotherapy. The aim of the present study was to assess neurocognitive functions of patients diagnosed with high-grade gliomas undergoing radiotherapy by using the NeuroCogFx® test and to examine relevant dose/volume parameters as well as patient characteristics potentially influencing the neurological baseline status and subsequent outcome. Methods: The cohort consisted of 44 astrocytoma World Health Organization grade III/IV patients. The NeuroCogFx® test was carried out on patients during (N = 44) and after (N = 21) irradiation. The test examines verbal/figural/short-term/working memory, psychomotorical speed, selective attention and verbal speed. The results were compared with regular patient and treatment data with an emphasis on the dose applied to the hippocampus. Results: Overall there were only slight changes in the median test results when comparing the baseline to the follow-up tests. In the ‘verbal memory test’ lower percentile ranks were achieved in left-sided tumors compared to right-sided tumors (p = 0.034). Dexamethasone intake during radiotherapy was significantly correlated with the difference between the two test batteries. Concerning figural memory, a correlation was detected between decreased figural recognition and the radiation dose to the left hippocampus (p = 0.045). Conclusion: We conclude that tumor infiltration of the hippocampus has an impact on neurocognitive function. However, treatment with radiotherapy seems to have less influence on cognitive outcome than expected.
CRIS-Team Scopus Importer:2023-09-13
Keywords: High-grade glioma; Hippocampal sparing; Hippocampus; Neurocognition; Radiation therapy